High selectivity of mutagenic action of synthetic polynucleotides - Alexandrov, Yu.N. (Биополимеры и клетка, 1999)
Solutions of high molecular weight syntetic poiyribo- and polydeoxyribonucleotides of known chemical structure injected into Drosophila melanogaster males caused a 6–17 fold increase of the overall frequency of the recessive lethals in the 2nd chromosome. Complementation analysis of the induced lethals showed an extremely high locus-specificity for some of these mutagens. Possible mechanisms of the mutagenic action of synthetic polynucleotides are discussed.